Modifikasi Model Pembelajaran Gerlach dan Ely Melalui Integrasi Nilai-Nilai Keislaman Sebagai Upaya Meningkatkan Kemampuan Representasi Matematis - Yusnita, Irda; Maskur, Ruhban; Suherman, Suherman (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
This study aims to determine whether the modification of learning models Gerlach and Ely through the integration of Islamic values can improve the ability of mathematical representation of learners. This research uses Pre-Experimental Design method with one-group pretest-posttest type. The prerequisite analysis test was performed by Liliefors test for normality and F test for homogeneity, then the data were analyzed by using N-Gain test and correlated t-test. The results of the analysis show that the mathematical representation of learners increases after using modified Gerlach and Ely learning models that are integrated with Islamic values rather than the mathematical representation of learners before using modified Gerlach and Ely learning models through the integration of Islamic values.